A new type of deep drawing die design and experimental results - Savas, Vedat; Secgin, Omer (Elsevier Sci Ltd, 2007)
Deep drawing is an important process used for producing cups from sheet metal in large quantities. The deep drawing is affected by many process variables, such as blank shapes, profile radius of punch and die, formability of materials and so on. Especially, in order to obtain the optimal products in deep drawing process, blank and die shapes are very important formability factor. In this study, we investigated the effects of blank holder and die shapes, using five kinds of blank holder and die shapes. We measured the distribution at blank holder force (BHF) according to the ratio of sheet metal drawing, under the constant conditions of profile radius of punch and die. Deriving from the experimental studies, it is clarified that angle of blank and die at deep drawing process influence blank holder force distribution and ratio of drawing. (c) 2006 Elsevier Ltd. All rights reserved.